2011
DOI: 10.1145/2068716.2068724
|View full text |Cite
|
Sign up to set email alerts
|

Net-length-based routability-driven power-aware clustering

Abstract: The state-of-the-art power-aware clustering tool, P-T-VPack, achieves energy reduction by localizing nets with high switching activity at the expense of channel width and area. In this study, we employ predicted individual postplacement net length information during clustering and prioritize longer nets. This approach targets the capacitance factor for energy reduction, and prioritizes longer nets for channel width and area reduction. We first introduce a new clustering strategy, W-T-VPack, which replaces the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…These studies involved algorithm-level modifications to existing clustering strategies. In our most recent work [Easwaran and Akoglu 2011], we completed a detailed analysis on power-aware clustering and showed how the state-of-the-art power-aware clustering algorithm P-TVPack [Lamoureux and Wilton 2003] benefited from predicted individual net length on deciding which LUT to cluster into the CLB. This study showed that incorporating net-length information to the clustering cost function enabled the algorithm to prioritize longer nets, target the capacitance factor for power reduction, and, at the same time, eliminate the channel-width overhead of the P-T-VPack.…”
Section: Introductionmentioning
confidence: 99%
“…These studies involved algorithm-level modifications to existing clustering strategies. In our most recent work [Easwaran and Akoglu 2011], we completed a detailed analysis on power-aware clustering and showed how the state-of-the-art power-aware clustering algorithm P-TVPack [Lamoureux and Wilton 2003] benefited from predicted individual net length on deciding which LUT to cluster into the CLB. This study showed that incorporating net-length information to the clustering cost function enabled the algorithm to prioritize longer nets, target the capacitance factor for power reduction, and, at the same time, eliminate the channel-width overhead of the P-T-VPack.…”
Section: Introductionmentioning
confidence: 99%